Cơ chế bệnh lý của tế bào gốc ung thư - Thăng, Nguyễn Duy; Hà , Chế Thị Cẩm; Lượng, Trần Văn; Trí, Tôn Thất Minh; Phương, Phạm Thị Ngọc; Túy, Trần Thị Phương (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.